Subsequent Oophorectomy and Ovarian Cancer after Hysterectomy for Benign Gynecologic Conditions at Chiang Mai University Hospital - Jitkunnatumkul A. (2017)
This study was undertaken to determine the incidence of subsequent oophorectomy due to ovarian pathology or ovarian cancer in women with prior hysterectomy for benign gynecologic conditions at Chiang Mai University Hospital. Medical records of women who underwent hysterectomy for benign gynecologic diseases and pre-cancerous lesions between January 1, 2004 and December 31, 2013 at Chiang Mai University Hospital were retrospectively reviewed. The incidence and indications of oophorectomy following hysterectomy were analyzed. During the study period, 1,035 women had hysterectomy for benign gynecologic conditions. Of these, 590 women underwent hysterectomy with bilateral salpingo-oophorectomy and 445 hysterectomy with bilateral ovarian preservation or unilateral salpingo-oophorectomy. The median age was 47 years (range, 11-75 years). Ten women (2.45 %) had subsequent oophorectomy for benign ovarian cysts. No case of ovarian cancer was found. The mean time interval between hysterectomy and subsequent oophorectomy was 43.1 months (range, 2-97 months) and the mean follow-up time for this patient cohort was 51 months (range, 1.3-124.9 months). According to our hospital-based data, the incidence of subsequent oophorectomy in women with prior hysterectomy for benign gynecologic conditions is low and all present with benign conditions.